Students’ Perceptions and Experiences on YouTube-mediated Self-regulated Learning - Umi Urmilah; Fauzi Miftakh; Iwan Ridwan (Universitas Muhammadiyah Enrekang, 2021)
Self-regulated learning is an independent and effective process where learners can fully control their learning. This narrative inquiry research aims to investigate the perspectives and experiences of EFL students who frequently watch YouTube videos to learn English outside of the classroom. The data from six participants of one of state university in Karawang, Indonedia were collected through questionnaires and semi-structured interviews. It was found that the majority of the students’ showed positive perceptions towards the use of YouTube for their goal commitment, affective, resource, and culture regulation. In contrast, the students showed negative perceptions towards the use of YouTube for their metacognitive and social regulation. Regarding students’ experiences, the findings revealed: (1) English skills that can be improved by frequently watching YouTube are listening and speaking skills; (2) the students tend to like the videos as feedback; (3) each student has a different preference on what videos and channels they usually watch to help them learn English; and (4) learning English using YouTube was considered to be more flexible, easier to be understood, and more enjoying than formal learning; nonetheless, formal learning can help the students practice their English more. In conclusion, using YouTube videos was considered to be helpful to accommodate the students’ self-regulated English learning.